A low-loss optical fiber preform and a method for manufacturing the same, and a low-loss optical fiber
Patent Information
- Application Number
- CN202611133420.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-09-11
AI Technical Summary
如果前期的脱水工艺不彻底,残留的羟基将与Ge结合,在1380nm波长处形成极强的吸收峰,并因其谐波影响1550nm窗口的衰减,引入瑞利散射损耗和羟基残留问题
[0030] The low-loss optical fiber preform and its preparation method, as well as the low-loss optical fiber provided in this application embodiment, can effectively reduce the hydroxyl content in the material by first performing a dehydroxylation treatment on the porous silica body; by performing a fluorine doping treatment and a first sintering on the first intermediate after dehydroxylation in a fluorine-containing gas, and by keeping the first sintering temperature lower than the second sintering temperature, the effective introduction of fluorine and the stable formation of the intermediate structure can be achieved; by further performing a second sintering on the second intermediate in a mixed atmosphere of inert gas and fluorine-containing gas, the preform can be further densified and loss-related defects can be suppressed, thereby obtaining a low-loss optical fiber preform and providing favorable conditions for the preparation of low-loss optical fibers.
Smart Images

Figure CN122725580A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of optical fiber materials, and in particular to a low-loss optical fiber preform and its preparation method, and a low-loss optical fiber. Background Technology
[0002] In modern communication networks, optical fiber is widely used in long-distance backbone network transmission, high-speed interconnection of data centers, 5G base station deployment, and industrial sensing systems. With the exponential growth of data traffic and the continuous improvement of communication speed, the market has placed higher demands on the transmission performance of optical fiber, especially the increasingly urgent need for ultra-low loss (attenuation coefficient less than 0.18dB / km) and stable optical properties (such as refractive index profile uniformity and macro-bending / micro-bending loss control).
[0003] As the core raw material for optical fiber manufacturing, the performance of optical fiber preforms directly determines the transmission quality and stability of optical fiber products. During the fabrication of optical fiber preforms, the refractive index difference (Δ) between the core and cladding is a key parameter for achieving optical waveguide performance. Traditional processes for fabricating optical fiber preforms rely on a high-purity silica (SiO2) matrix, and the Δ value is controlled by doping with high-refractive-index materials (such as GeO2) or low-refractive-index materials (such as F).
[0004] However, in the porous body before sintering, Ge exists in large quantities in the form of Ge-OH bonds. If the initial dehydration process is incomplete, the residual hydroxyl groups will combine with Ge, forming an extremely strong absorption peak at 1380 nm. This peak, due to its harmonic effects, attenuates the 1550 nm window, introducing Rayleigh scattering loss and hydroxyl residue issues. Fluorine doping, on the other hand, faces challenges such as uneven fluorine distribution and weakening of the glass network structure.
[0005] In addition, the high-temperature sintering process used for alkali metal doping in traditional processes can easily cause alkali metal impurities (such as Na and K) to diffuse into the core layer, further aggravating the attenuation of optical signals.
[0006] Therefore, there is an urgent need to develop a method for preparing optical fiber preforms that can control the uniformity of fluorine doping and suppress alkali metal migration, in order to solve the problems of refractive index distribution distortion and impurity absorption loss, thereby meeting the demand for large-scale production of low-loss optical fibers. Summary of the Invention
[0007] This application provides a low-loss optical fiber preform and its preparation method, as well as a low-loss optical fiber, to ensure stable material performance while improving the optical quality of the preform.
[0008] In a first aspect, embodiments of this application provide a method for preparing a low-loss optical fiber preform, comprising:
[0009] The silica porous body was subjected to dehydroxylation treatment to obtain the first intermediate;
[0010] The first intermediate is subjected to fluorine doping treatment and first sintering in a fluorine-containing gas to obtain the second intermediate;
[0011] The second intermediate is subjected to a second sintering in a mixed atmosphere of inert gas and fluorine-containing gas to obtain the low-loss optical fiber preform.
[0012] The temperature of the first sintering is lower than the temperature of the second sintering.
[0013] In one possible implementation, the silica porous body comprises a core rod and a deposited layer having a density of 0.28 g / cm³. 3 -0.40g / cm 3 ;
[0014] And / or, the second intermediate contains fluorine, and the radial concentration difference of the fluorine in the second intermediate is less than or equal to 8%;
[0015] And / or, the porosity of the second intermediate is less than or equal to 5%.
[0016] In one possible implementation, the dehydrogenation treatment is carried out at a temperature of 1100°C-1300°C.
[0017] In one possible implementation, the heating rate of the dehydrogenation treatment is 10°C / min to 15°C / min.
[0018] In one possible implementation, the temperature of the fluorine doping treatment is less than or equal to the temperature of the dehydroxylation treatment.
[0019] In one possible implementation, the temperature of the first sintering is greater than or equal to the temperature of the fluorine doping treatment.
[0020] In one possible implementation, a first cooling and / or a second cooling process is further included after the second sintering:
[0021] The cooling rate of the first cooling is 50℃ / min-100℃ / min;
[0022] The starting temperature for the second cooling is 800℃-1000℃.
[0023] Secondly, embodiments of this application provide a low-loss optical fiber preform, prepared by the above-described preparation method.
[0024] In one possible implementation, the porosity of the low-loss optical fiber preform is less than or equal to 0.1%;
[0025] And / or, the low-loss optical fiber preform is doped with fluorine, and the radial doping depth deviation of the fluorine in the low-loss optical fiber preform is less than or equal to 0.3%.
[0026] In one possible implementation, the low-loss optical fiber preform comprises alkali metal ions;
[0027] The radial diffusion depth of the alkali metal ions in the low-loss optical fiber preform is less than or equal to 5 μm.
[0028] And / or, the low-loss optical fiber preform includes a core, wherein the concentration of the alkali metal ions in the core is less than or equal to 0.6 ppb.
[0029] Thirdly, embodiments of this application provide a low-loss optical fiber, which is prepared by stretching the aforementioned low-loss optical fiber preform; the radial distribution concentration difference of fluorine in the low-loss optical fiber is less than or equal to 2.5%.
[0030] The low-loss optical fiber preform and its preparation method, as well as the low-loss optical fiber provided in this application embodiment, can effectively reduce the hydroxyl content in the material by first performing a dehydroxylation treatment on the porous silica body; by performing a fluorine doping treatment and a first sintering on the first intermediate after dehydroxylation in a fluorine-containing gas, and by keeping the first sintering temperature lower than the second sintering temperature, the effective introduction of fluorine and the stable formation of the intermediate structure can be achieved; by further performing a second sintering on the second intermediate in a mixed atmosphere of inert gas and fluorine-containing gas, the preform can be further densified and loss-related defects can be suppressed, thereby obtaining a low-loss optical fiber preform and providing favorable conditions for the preparation of low-loss optical fibers. Attached Figure Description
[0031] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0032] Figure 1 A schematic diagram illustrating the fabrication scenario of the low-loss optical fiber preform provided in this application;
[0033] Figure 2 Radial refractive index distribution diagram of the low-loss optical fiber preform provided in Embodiment 1 of this application;
[0034] Figure 3 A radial refractive index distribution diagram of the optical fiber preform provided in Embodiment 10 of this application;
[0035] Figure 4 The radial refractive index distribution of the optical fiber preform provided in Comparative Example 1 of this application is shown.
[0036] Figure label:
[0037] 001-Gas cylinder; 002-Pressure controller; 003-Flow meter; 004-Vacuum angle valve; 005-Sintering furnace.
[0038] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0039] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numbers in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. Rather, they are merely examples of apparatuses and methods consistent with some aspects of this application as detailed in the appended claims.
[0040] Optical fiber preform fabrication technology belongs to the field of optical fiber communication material manufacturing and is mainly used in the fabrication process of low-loss transmission optical fibers. This type of application typically involves processes such as chemical treatment, atmosphere control, and sintering densification of porous silica to obtain preforms that meet communication performance requirements, which are then further used to draw optical fibers.
[0041] In the existing low-loss optical fiber preform fabrication process, it is usually necessary to first remove the hydroxyl groups from the silicon oxide matrix to reduce the transmission loss caused by the hydroxyl absorption bands. At the same time, fluorine is introduced through a fluorine-containing atmosphere to adjust the refractive index of the material and improve its optical performance. Subsequently, a dense preform structure is formed by sintering. The basic principle of this approach is to achieve impurity removal, composition adjustment, and structural densification by combining gas-phase treatment and heat treatment.
[0042] However, in existing processes, the connection between dehydroxylation, fluorine doping, and sintering, as well as the temperature control at different sintering stages, are often not reasonable enough. This can easily lead to insufficient fluorine doping efficiency, uneven fluorine distribution, or adverse losses during high-temperature processes, thus affecting the densification effect and final loss level of the preform. Especially when it is necessary to simultaneously achieve low hydroxyl content and stable fluorine doping effect, improper processing sequence or atmosphere settings often cause fluctuations in material properties, making it difficult to consistently obtain low-loss products, thereby adversely affecting the subsequent optical fiber transmission performance and product consistency.
[0043] The method for preparing low-loss optical fiber preforms provided in this application involves first dehydroxylating a porous silica body to obtain a first intermediate, then doping the first intermediate with fluorine in a fluorine-containing gas and performing a first sintering to obtain a second intermediate, and then performing a second sintering of the second intermediate in a mixed atmosphere of inert gas and fluorine-containing gas, wherein the temperature of the first sintering is lower than the temperature of the second sintering, thereby providing a feasible technical path for obtaining low-loss optical fiber preforms.
[0044] The technical solution of this application and how the technical solution of this application solves the above-mentioned technical problems are described in detail below with specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments. The embodiments of this application will now be described with reference to the accompanying drawings.
[0045] Figure 1 This is a schematic diagram illustrating the fabrication scenario of the low-loss optical fiber preform provided in this application, as shown below. Figure 1 As shown, the equipment used to realize the fabrication method of low-loss optical fiber preform includes a gas cylinder 001, a pressure controller 002, a flow meter 003, a vacuum angle valve 004, and a sintering furnace 005. The fabrication method includes: dehydroxylating a porous silica body to obtain a first intermediate; doping the first intermediate with fluorine in a fluorine-containing gas and performing a first sintering to obtain a second intermediate; and performing a second sintering of the second intermediate in a mixed atmosphere of an inert gas and a fluorine-containing gas to obtain a low-loss optical fiber preform; the temperature of the first sintering is lower than the temperature of the second sintering.
[0046] Specifically, the silica porous body can be obtained by external vapor deposition, axial vapor deposition, modified chemical vapor deposition, porous glass molding, or gel casting followed by drying. In one possible embodiment, the main raw material of the silica porous body is high-purity SiO2 (Silicon Dioxide), and the total amount of metal impurities is controlled below ppm (par(Argon)tsper million). The initial pore structure of the porous body remains connected so that the subsequent reactive gases can enter the internal channels and complete the dehydroxylation and fluorine doping.
[0047] The dehydroxylation treatment can be carried out in a chlorine-containing atmosphere, a fluorine-containing dehydration atmosphere, or a combination thereof. For example, a combination system of Cl2, HCl, or SiCl4 vapor and carrier gas can be used to cause the hydroxyl groups existing in the Si-OH form in the porous material to undergo substitution or volatile transformation, and water, HCl, or related volatile byproducts are discharged under heating conditions. In particular, the dehydrogenation treatment removes the hydroxyl groups in the form of these substances, thereby reducing the optical loss caused by the hydroxyl absorption band in subsequent rod making and providing a stable reaction basis for subsequent fluorine doping and sintering.
[0048] Subsequently, the first intermediate is subjected to fluorine doping treatment in a fluorine-containing gas while undergoing a first sintering process to obtain the second intermediate. The fluorine-containing gas can serve as the atmosphere source for the fluorine doping treatment, introducing fluorine into the material. After fluorine doping is completed or during the first sintering process, the porous body undergoes preliminary densification and pore shrinkage is achieved.
[0049] Limiting the first sintering temperature to a temperature lower than the subsequent second sintering temperature serves two purposes: firstly, it prevents the rapid volatilization of fluorine at excessively high temperatures before the fluorine doping has fully stabilized; secondly, it allows the material to complete the skeleton rearrangement and defect repair at a lower temperature, thus preserving sufficient structural uniformity for subsequent high-temperature densification.
[0050] Next, the second intermediate is subjected to a second sintering in a mixed atmosphere of inert and fluorine-containing gases to obtain a low-loss optical fiber preform. The second sintering temperature is higher than the first sintering temperature, enabling the second intermediate to further achieve pore closure, microstructure rearrangement, and overall densification under higher thermal energy input. The continued presence of fluorine-containing gas in the mixed atmosphere allows the material to maintain a certain fluorine balance during the second sintering stage, preventing excessively rapid fluorine loss from the surface or near-surface layers, thus resulting in a more consistent refractive index and composition distribution in the obtained low-loss optical fiber preform.
[0051] The low-loss optical fiber preform formed by the above steps has a low hydroxyl content, uniform fluorine distribution and high density, which can provide a stable refractive index profile and a low absorption loss basis for subsequent optical fiber drawing.
[0052] In some specific embodiments, the silica porous body includes a core rod and a deposited layer, the density of which is 0.28 g / cm³. 3 -0.40g / cm 3 .
[0053] In the preparation process, a porous silica body comprising a core rod and a deposited layer is first prepared, and the density of the deposited layer is controlled at 0.28 g / cm³. 3 -0.40g / cm 3 This ensures that the deposited layer retains sufficient porosity to facilitate subsequent gas diffusion and impurity migration, while avoiding excessively low density that could lead to a loose structure and uncontrolled shrinkage during subsequent sintering.
[0054] For example, the density of the deposited layer can be 0.28 g / cm³. 3 0.30g / cm 3 0.22g / cm 3 0.34g / cm 3 0.36 g / cm³, 0.38 g / cm³ 3 0.40 g / cm 3 Or a range consisting of any two of them.
[0055] Subsequently, the porous silica is subjected to dehydroxylation treatment to form a first intermediate. In this treatment, hydroxyl groups are removed by means of temperature and atmosphere control, while the diffusion and migration range of alkali metal ions in the first intermediate is effectively controlled.
[0056] In some specific embodiments, the second intermediate contains fluorine, and the radial concentration difference of fluorine in the second intermediate is less than or equal to 8%.
[0057] Next, the first intermediate is subjected to fluorine doping treatment in a fluorine-containing gas and then subjected to the first sintering, so that the fluorine element enters the interior of the porous body and tends to be uniformly distributed during the initial densification process; by controlling the radial concentration difference of the fluorine element in the second intermediate to less than or equal to 8%, radial component fluctuations can be suppressed, thereby reducing the dispersion of subsequent optical properties.
[0058] In some specific implementations, the porosity of the second intermediate is less than or equal to 5%.
[0059] After the first intermediate is sintered, the porosity of the second intermediate is less than or equal to 5%, which indicates that the structure has formed a high initial density and provides a stable framework for the subsequent second sintering in a mixed atmosphere of inert gas and fluorine-containing gas.
[0060] Because the aforementioned deposit density, alkali metal ion diffusion state, fluorine element distribution uniformity and porosity complement each other, the dehydroxylation, fluorine doping and sintering processes can be continuously connected, thereby obtaining a low-loss optical fiber preform with uniform structure and good density.
[0061] In some specific implementations, the dehydrogenation treatment temperature is 1100℃-1300℃.
[0062] In some specific implementations, the dehydrogenation treatment time is 1-2 hours.
[0063] In some embodiments, the silica porous body is placed in a dehydroxylation furnace and heated to 1100℃-1300℃ in a dry atmosphere or a mixed atmosphere of helium and oxygen, and held for 1-2 hours. This allows the hydroxyl groups inside the porous body and on the surface of the pores to be removed at high temperature and carried out by the gas flow, forming a first intermediate. Controlling the temperature at 1100℃-1300℃ ensures that the hydroxyl removal reaction proceeds fully, while avoiding incomplete dehydroxylation due to excessively low temperatures or excessive shrinkage of the skeleton and abnormal changes in the pore structure due to excessively high temperatures. Controlling the time to 1-2 hours achieves a balance between dehydroxylation efficiency and thermal history control, reducing the hydroxyl content to an acceptable level for subsequent fluorine doping and sintering. If the holding time is too short, the hydroxyl groups in the internal diffusion-restricted areas will be difficult to remove completely; if it is too long, it will increase the energy consumption of heat treatment and amplify material structural fluctuations. Therefore, the above time range, combined with the temperature range, can achieve stable dehydroxylation.
[0064] For example, the temperature of the dehydrogenation treatment can be a range of 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, or any combination thereof.
[0065] For example, the dehydrogenation treatment time can be a range of 1 h, 1.5 h, 2 h, or any combination thereof.
[0066] In some specific implementations, the temperature distribution difference of the dehydrogenation process is less than or equal to 10°C.
[0067] In another embodiment, controlling the temperature distribution difference within the furnace or reaction zone during the dehydroxylation process within a small range ensures uniform heating of all parts of the porous silica, preventing uneven hydroxyl residue, differences in pore shrinkage, and fluctuations in subsequent fluorine doping depth caused by localized overheating or underheating. By reducing the temperature distribution difference, the dehydroxylation reaction proceeds more synchronously in both the radial and axial directions, thereby improving the compositional and structural uniformity of the first intermediate and providing a consistent initial state for subsequent fluorine doping and sintering densification. This synergistic control of temperature, time, and thermal field uniformity enables the dehydroxylation process to stably obtain a first intermediate with low hydroxyl content and uniform structure, thus ensuring the continuity of subsequent processes and product consistency.
[0068] In some specific implementations, the heating rate of the dehydrogenation process is 10℃ / min-15℃ / min.
[0069] In practice, the porous silica body can be placed in a dehydroxylation furnace and heated to the dehydroxylation temperature at a rate of 10℃ / min-15℃ / min under a set atmosphere, and held at the target temperature for a corresponding time. This allows the hydroxyl groups inside the porous body to be gradually removed, resulting in a more uniform temperature distribution. Because this heating range can balance heat transfer rate and internal diffusion rate, the dehydroxylation reaction and structural shrinkage process can be matched, promoting the formation of a first intermediate with a uniform pore structure and low stress distribution. The first intermediate is more stable, and during subsequent fluorine doping and sintering in a fluorine-containing gas, it can more uniformly accept the entry of fluorine and the densification effect of sintering, thereby improving the compositional consistency and optical stability of the preform.
[0070] For example, the heating rate of the dehydrogenation treatment can be a range of 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, or any combination thereof.
[0071] In some specific implementations, the temperature of the fluorine doping treatment is less than or equal to the temperature of the dehydroxylation treatment.
[0072] In this embodiment, the temperature of the fluorine doping treatment is less than or equal to the temperature of the dehydroxylation treatment, which helps to ensure the radial uniformity of fluorine doping, improve the effective doping efficiency of fluorine, suppress the high-temperature volatilization loss of fluorine, and avoid excessive structural defects and bubble formation.
[0073] In some embodiments, the temperature for fluorine doping treatment is 800°C-1100°C.
[0074] Controlling the fluorine doping temperature within the range of 800℃-1100℃ ensures that fluorine molecules possess sufficient activation energy to enter the pores of the silica porous body and achieve effective doping. Simultaneously, it suppresses insufficient diffusion and uneven fluorine distribution at excessively low temperatures. This temperature range matches the first sintering process, allowing for a relatively uniform distribution of fluorine between particles and within the pores, providing a stable foundation for densification and refractive index adjustment during the subsequent second sintering. If the temperature is too low, the fluorine diffusion depth is insufficient, making it difficult to achieve the component distribution required for low loss; if the temperature is too high, premature fluorine escape or local structural collapse can easily occur, thus weakening the fluorine doping effect. By limiting the temperature within this range, the fluorine doping reaction and the evolution of the porous body structure can achieve better synergy, thereby stably obtaining a second intermediate with a uniform fluorine content distribution.
[0075] For example, the temperature for fluorine doping treatment can be a range of 800°C, 900°C, 1000°C, 1100°C, or any combination thereof.
[0076] In some specific implementations, the fluorine doping treatment time is 200-400 minutes.
[0077] Controlling the fluorine doping treatment time to 200-400 minutes ensures sufficient contact and diffusion reaction time between the fluorine-containing gas and the first intermediate, allowing for a continuous and uniform concentration gradient of fluorine in the radial direction. This avoids insufficient fluorine doping due to too short a treatment time, or excessive fluorine source consumption and increased heat exposure due to too long a time. This time range is typically matched to the bulk density, pore structure, and gas flow rate, enabling sufficient infiltration and fixation of fluorine before the first sintering, thereby reducing the risk of increased radial concentration variation of fluorine during the subsequent second sintering process. The resulting second intermediate exhibits more stable compositional homogeneity and a more suitable porosity, thus creating conditions for obtaining low-loss optical fiber preforms.
[0078] For example, the fluorine doping treatment time can be a range of 200 min, 250 min, 300 min, 350 min, 400 min, or any combination thereof.
[0079] In some specific implementations, the temperature of the first sintering is greater than or equal to the temperature of the fluorine doping treatment.
[0080] Because fluorine mainly enters the first intermediate through physical adsorption and weak bonding during the initial fluorine doping treatment, its binding force is relatively weak. Therefore, in this embodiment, by controlling the first sintering temperature to be greater than or equal to the fluorine doping treatment temperature, the fluorine doping can be fixed after the fluorine doping treatment, suppressing the reverse volatilization of fluorine. Simultaneously, the first intermediate gradually shrinks from the fluorine doping treatment temperature to the first sintering temperature, achieving a gradual shrinkage from the surface inwards. By controlling the first sintering temperature to be greater than or equal to the fluorine doping treatment temperature, the pores can be gradually closed, completing gradient pre-densification, preventing the formation of closed pores and bubbles, promoting structural relaxation, and achieving a uniform fluorine distribution.
[0081] In some embodiments, the temperature of the first sintering is 1200℃-1300℃.
[0082] In some embodiments, the first sintering time is 40 min to 80 min.
[0083] In one specific implementation, after the first intermediate is placed in sintering furnace 005, it is first heated to 1200℃-1300℃ under continuous fluorine gas supply and held for 40min-80min. This allows it to undergo preliminary densification and synergistic introduction of fluorine in the fluorine environment, resulting in a second intermediate with reduced porosity and more uniform compositional distribution. By limiting both temperature and time within the aforementioned range, the first sintering can be coupled with the fluorine doping treatment, allowing fluorine to enter the material while the framework still has rearrangement potential and be relatively stably fixed. This provides a foundation for the subsequent second sintering at higher temperatures, resulting in a homogeneous composition and stable structure, thus contributing to the acquisition of low-loss optical fiber preforms.
[0084] For example, the temperature of the first sintering can be a range of 1200°C, 1250°C, 1300°C or any combination thereof; the time of the first sintering can be a range of 40 min, 50 min, 60 min, 70 min, 80 min or any combination thereof.
[0085] In some specific implementations, the second sintering temperature is 1400℃-1500℃.
[0086] In some specific implementations, the second sintering time is 30-60 minutes.
[0087] In this embodiment, the second sintering refers to the process of further high-temperature densification of the second intermediate after fluorine doping and the first sintering. Its function is to continue to eliminate residual pores in the mixed atmosphere of inert gas and fluorine-containing gas, and to maintain the stable distribution of fluorine in the material.
[0088] The second sintering temperature is controlled at 1400℃-1500℃, which allows the second intermediate to undergo further bonding and rearrangement under the action of higher thermal driving force, thereby promoting the growth of interparticle necks and pore closure. If the temperature is below 1400℃, the densification driving force is insufficient and the residual pores are not easily eliminated. If the temperature is above 1500℃, it is easy to cause excessive structural shrinkage and loss of fluorine components, affecting the refractive index control effect and low loss performance.
[0089] For example, the second sintering temperature can be a range of 1400°C, 1420°C, 1450°C, 1480°C, 1500°C, or any combination thereof.
[0090] By controlling the second sintering time to 30-60 minutes, the thermal effect can continue until the internal gas is discharged, the pores further collapse, and the structure is homogenized. If the time is too short, the second intermediate will be difficult to achieve the required density. If the time is too long, it will increase the risk of fluorine volatilization and structural coarsening.
[0091] For example, the second sintering time can be a range of 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, or any combination thereof.
[0092] Therefore, the second sintering temperature is 100℃-150℃ lower than that of the traditional process, and the holding time is strictly controlled within 30min-60min, which shortens the time by more than 50% compared with the traditional process. The coordinated control of the second sintering temperature and time enables the second intermediate to achieve a higher degree of density while maintaining a stable fluorine distribution, thereby obtaining a low-loss optical fiber preform with lower porosity and better optical uniformity.
[0093] In some specific implementations, the flow rate of the fluorine-containing gas is 1L / min-5L / min.
[0094] In this process, during the second sintering of the second intermediate, an inert gas is first introduced to establish a stable protective atmosphere, followed by the introduction of a fluorine-containing gas to form a mixed atmosphere for the second sintering. Controlling the flow rate of the fluorine-containing gas between 1 L / min and 5 L / min ensures a sufficient supply of fluorine within the sintering zone, allowing the residual pores and surface area to continuously receive fluorination regulation. This avoids insufficient fluorine distribution due to excessively low flow rate, or atmospheric disturbance and component loss due to excessively high flow rate.
[0095] For example, the flow rate of the fluorine-containing gas can be a range of 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, or any combination thereof.
[0096] In some specific implementations, the flow rate of the inert gas is 0.5 m / s to 1.0 m / s.
[0097] Controlling the flow rate of inert gas at 0.5 m / s-1.0 m / s can enhance atmosphere renewal and homogenization, maintain stable coating of the sintering zone, and thus suppress the intrusion of external impurities and local overheating.
[0098] For example, the flow rate of the inert gas can be a range of 0.5 m / s, 0.6 m / s, 0.7 m / s, 0.8 m / s, 0.9 m / s, 1.0 m / s, or any combination thereof.
[0099] The synergistic effect of the two factors enables the fluorine-containing gas to diffuse uniformly in a stable gas flow field and participate in the further densification of the second intermediate, thereby improving the fluorine element distribution and sintering consistency.
[0100] In some specific implementations, the temperature difference in the second sintering temperature distribution is less than or equal to 5°C.
[0101] During the second sintering process, controlling the temperature difference within 5°C ensures that all parts of the second intermediate receive approximately uniform heat input, preventing asynchronous densification, uneven fluorine volatilization, or structural stress concentration caused by excessive local temperature differences. Since the second sintering occurs at a higher temperature range, the uniformity of the thermal field directly determines pore closure, component rearrangement, and fluorine retention. Therefore, by limiting the temperature difference, the second intermediate can undergo further sintering and densification synchronously as a whole, ultimately yielding a low-loss optical fiber preform with lower porosity and more uniform composition.
[0102] In some specific embodiments, after the second sintering, a first cooling and / or a second cooling are further included; the cooling rate of the first cooling is 50°C / min-100°C / min.
[0103] In this embodiment, the first cooling refers to a controlled cooling process performed on the preform after the second sintering, causing the preform to descend from the temperature range of the second sintering at a cooling rate of 50°C / min to 100°C / min. Controlling the cooling rate within this range allows the dense structure formed at high temperatures to smoothly release thermal stress, avoiding microcracks, internal stress concentration, or structural springback caused by sudden cooling. Simultaneously, it suppresses uneven migration of the fluorine-doped components in the initial cooling stage, thereby maintaining the low-loss structural stability obtained after the second sintering. This cooling rate is chosen to match the material's still highly active thermal state after the second sintering, balancing cooling efficiency with structural integrity, thus ensuring the dimensional stability and optical consistency of the preform during subsequent processing.
[0104] For example, the cooling rate of the first cooling can be a range of 50°C / min, 60°C / min, 70°C / min, 80°C / min, 90°C / min, 100°C / min, or any combination thereof.
[0105] In some specific implementations, the starting temperature of the second cooling is 800°C-1000°C.
[0106] The second cooling refers to further cooling starting at a specific temperature point after the second sintering, with the initial temperature set at 800℃-1000℃. When the preform cools from the second sintering temperature to this initial temperature range, the pore closure, component diffusion, and stress relaxation within the material have entered different stages. Switching to the second cooling at this point allows for a more controlled release of residual heat, preventing excessive volatilization or distribution shift of the fluorine components due to prolonged exposure to high temperatures. Limiting the starting temperature of the second cooling to this range allows for seamless coordination with the first cooling, making the thermal history after the second sintering more controllable, thereby improving the preform's densification retention and low-loss performance stability.
[0107] For example, the starting temperature of the second cooling can be a range of 800°C, 900°C, 1000°C, or any combination thereof.
[0108] The method for preparing low-loss optical fiber preforms provided in this application first reduces hydroxyl impurities by dehydroxylation, then uses fluorine-containing gas to complete fluorine doping and preliminary densification, and then completes final sintering at a higher temperature in combination with a mixed atmosphere. This allows the impurity removal, component adjustment and structural densification to be matched in time, thereby forming a low-loss optical fiber preform with uniform fluorine distribution, low porosity and stable thermal structure.
[0109] This application also provides a low-loss optical fiber preform, which is prepared by the above-described preparation method, wherein the radial distribution concentration difference of fluorine in the low-loss optical fiber is less than or equal to 2.5%.
[0110] The low-loss characteristic of the low-loss optical fiber preform in this application stems from the synergistic constraint among dehydroxylation, fluorine doping, and staged sintering. The reaction mechanism is as follows: firstly, dehydroxylation reduces the absorption loss of Si-OH near 1.39 μm and in related wavelengths, and reduces the chance of competitive reactions between hydroxyl groups and fluorine-containing species, thus improving the effective fluorine utilization rate in the subsequent fluorine doping stage. Based on this, a first sintering under a fluorine-containing atmosphere is performed, allowing fluorine introduction to occur simultaneously with primary shrinkage. Before the pores are fully closed, the material possesses a more sufficient gas-solid exchange interface, making it easier for fluorine to enter the porous silica body. Subsequently, a second sintering at a temperature higher than the first sintering temperature is used, while maintaining a mixed atmosphere of inert and fluorine-containing gases. This suppresses fluorine escape during the high-temperature densification process, ultimately resulting in a denser preform with a more stable fluorine content distribution and fewer defects.
[0111] Based on the above analysis, it can be seen that the process limitations are directly reflected in the product structure characteristics, that is, the preforms have a lower residual hydroxyl level, fewer bubbles and closed pore defects, and higher axial consistency, which corresponds to lower absorption loss and scattering loss after subsequent fiber drawing.
[0112] The low-loss optical fiber preform in this application can be in a transparent or semi-transparent dense glassy state after sintering, with no through cracks, obvious streaks, or visible bubble aggregation on a macroscopic scale, and the number of closed pores and residual open pores is controlled on a microscopic scale. Its residual hydroxyl and fluorine content can be characterized by detection methods.
[0113] The preparation method provided in this application realizes the continuous transformation from a loose skeleton to a dense rod, and simultaneously completes impurity reduction, component adjustment and network homogenization during the transformation process, so that the final preform not only meets the mechanical integrity required by the subsequent drawing process, but also meets the material requirements of communication optical fibers for low background loss.
[0114] In some specific implementations, the porosity of the low-loss optical fiber preform is less than or equal to 0.1%.
[0115] In some specific implementations, the low-loss optical fiber preform is doped with fluorine, and the radial doping depth deviation of fluorine in the low-loss optical fiber preform is less than or equal to 0.3%.
[0116] The radial concentration distribution of fluorine in low-loss optical fiber preforms affects their radial refractive index distribution. By controlling the radial doping depth deviation of fluorine in the preform to be less than or equal to 0.3%, and combining this with segmented gas supply, zoned deposition, and graded heating, the refractive index fluctuations at each radial position are reduced. This process achieves a smooth transition of the refractive index profile, suppresses mode coupling and scattering losses caused by radial inhomogeneity, and also reduces structural distortion caused by component migration during sintering and drawing.
[0117] like Figure 2 As shown, in the low-loss optical fiber preform provided in this application, the refractive index of its core and the refractive index of its surface remain at the same level, without significant fluctuations.
[0118] In some specific embodiments, the low-loss optical fiber preform includes alkali metal ions; the radial diffusion depth of the alkali metal ions in the low-loss optical fiber preform is less than or equal to 300 μm.
[0119] In this low-loss optical fiber preform, the introduced alkali metal ions can be one or more of lithium, sodium, potassium, rubidium, or cesium. Their role is to make minor adjustments to the glass network and assist in ion balance and structural stability at specific process stages. By limiting the alkali metal ions to a low content and shallow diffusion state, significant refractive index disturbances or local structural relaxations within the low-loss optical fiber preform can be avoided, thereby suppressing additional absorption and scattering losses caused by alkali metal ion migration.
[0120] Specifically, the radial diffusion depth of alkali metal ions is less than or equal to 300 μm, meaning that they migrate only shallowly on the surface of the low-loss optical fiber preform or in locally doped regions. This parameter is achieved by controlling the fluorine doping temperature, the first sintering temperature, the holding time, and the cooling rate. For example, pre-densification or sintering at lower temperatures and for shorter times can effectively limit the radial diffusion of alkali metal ions. The reaction mechanism lies in the fact that low temperature, short time, and controlled atmosphere can reduce the migration energy of alkali metal ions, thereby inhibiting the deep penetration of alkali metal ions into the main glass network and minimizing their disturbance to the refractive index distribution and material uniformity.
[0121] For example, the radial diffusion depth of alkali metal ions in low-loss optical fiber preforms can be 80 μm, 105 μm, 110 μm, 118 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 150 μm, 160 μm, 170 μm, 200 μm, 250 μm, 300 μm, etc.
[0122] In some specific embodiments, the low-loss optical fiber preform includes a core, wherein the concentration of alkali metal ions in the low-loss optical fiber preform core is less than or equal to 0.6 ppb.
[0123] It is understood that alkali metal ions are the root cause of infrared absorption loss. Once they diffuse into the core in large quantities, they directly increase the fundamental loss of the optical fiber and degrade the communication transmission distance. Therefore, the preparation method provided in this application not only controls the temperature of the dehydrogenation treatment to reduce the diffusion rate of alkali metal ions and effectively control their migration range, but also introduces a first sintering treatment between the fluorine doping treatment and the second sintering treatment, and controls the temperature of the first and second sintering treatments to control the concentration of alkali metal ions in the core of the low-loss optical fiber preform to less than or equal to 0.6 ppb. This significantly reduces the impact of alkali metal ions on the chemical purity, thermal stability, and optical transmittance of the glass, and eliminates additional losses at short wavelengths.
[0124] In addition, suppressing the diffusion of external alkali metal ions into the core results in a lower density of low-alkali matrix defects, leading to better long-term loss stability of the optical fiber and improved resistance to hydrogen aging and radiation.
[0125] As can be seen from the above analysis, the preparation method provided in this application achieves synergistic design of alkali metal ions: through the dual constraints of shallow diffusion and low concentration, their continuous migration or enrichment during sintering and densification is avoided. This ensures that the low-loss optical fiber preform has a dense structure and uniform composition while further reducing optical loss caused by impurities, thereby ensuring that the subsequently drawn optical fiber has more stable low-loss transmission performance and better batch consistency.
[0126] For example, the concentration of alkali metal ions in the core can be 0.01 ppb, 0.05 ppb, 0.08 ppb, 0.1 ppb, 0.13 ppb, 0.2 ppb, 0.3 ppb, 0.4 ppb, 0.5 ppb, 0.6 ppb, etc.
[0127] In some embodiments, the core diameter of the low-loss optical fiber preform is 40mm-60mm, specifically, it can be a range of 40mm, 42mm, 44mm, 46mm, 48mm, 50mm, 52mm, 54mm, 56mm, 58mm, 60mm or any combination thereof.
[0128] This application also provides a low-loss optical fiber, which is prepared by stretching the aforementioned low-loss optical fiber preform.
[0129] When optical fibers are fabricated by stretching low-loss fiber preforms, the low hydroxyl content, relatively uniform fluorine distribution, and dense structure formed in the preform through dehydroxylation, fluorine doping, and staged sintering can be inherited into the optical fiber. This results in lower hydroxyl absorption loss and a stable refractive index distribution in the drawn fiber. The synergistic effect of the temperature gradient and atmosphere during the first and second sintering processes helps reduce adverse fluorine losses and improves the overall compaction quality of the preform. This leads to more stable dimensional control and performance during the fiber drawing process, thereby reducing fiber transmission loss and improving product consistency. Therefore, it better meets the requirements of low-loss communication transmission applications.
[0130] The low-loss optical fiber provided in this embodiment can perform the method provided in the above-described method embodiments. Its implementation principle and technical effect are similar, and will not be described in detail here.
[0131] The technical solution of this application will be further described below using specific embodiments.
[0132] Example 1
[0133] A low-loss optical fiber preform is prepared by the following method:
[0134] Preparation of porous silica: High-purity SiCl4 was used as the deposition material, which was decomposed into high-purity SiO2 in an oxyhydrogen flame and deposited on the surface of a mandrel. The deposition temperature was 1200℃ and the deposition time was 600 min. High-purity oxygen (purity ≥99.999%) was introduced during the deposition process to obtain porous silica with a diameter of 120 mm and a length of 1600 mm.
[0135] Dehydrogenation treatment: The obtained loose silica body is placed in a sintering furnace, using a He / O2 mixed gas as a protective atmosphere, while CF4 is introduced at a flow rate of 3 L / min. The temperature in the sintering furnace is raised to 1100℃ at a heating rate of 10℃ / min and held for 1 hour. At this time, the temperature distribution difference in the sintering furnace is 10℃. The hydroxyl groups react with oxygen to form water vapor, which is then discharged to obtain the first intermediate.
[0136] Fluorine doping treatment: After the dehydrogenation treatment, the temperature in the sintering furnace is adjusted to 1000℃ and held for 200 minutes for fluorine doping; after the fluorine doping is completed, the temperature in the sintering furnace is adjusted to 1280℃ and held for 40 minutes for the first sintering to achieve pre-densification and obtain the second intermediate.
[0137] Second sintering process: High-purity He (flow rate of 0.5 m / s) was used as the protective gas, and fluorine was continuously passed through for 3 hours; the temperature in the sintering furnace was adjusted to 1400℃ and held for 60 minutes for the second sintering. At this time, the temperature distribution difference in the sintering furnace was 5℃; after the second sintering was completed, the temperature in the sintering furnace was reduced to 800℃ at a cooling rate of 50℃ / min, and then naturally cooled to room temperature to obtain a low-loss optical fiber preform.
[0138] Example 2
[0139] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the heating rate during the dehydrogenation treatment is 15°C / min and the temperature difference in the furnace is 10°C.
[0140] Example 3
[0141] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the heating rate during the dehydrogenation treatment is 5°C / min and the temperature difference in the furnace is 10°C.
[0142] Example 4
[0143] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 2, except that the heating rate during the dehydrogenation treatment is 20°C / min and the temperature difference in the furnace is 10°C.
[0144] Example 5
[0145] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the temperature during the dehydrogenation treatment is 1300℃.
[0146] Example 6
[0147] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the temperature during the dehydrogenation treatment is 1000℃.
[0148] Example 7
[0149] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 5, except that the temperature during the dehydrogenation treatment is 1400℃.
[0150] Example 8
[0151] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the temperature during fluorine doping is 800°C and the treatment time is 400 min.
[0152] Example 9
[0153] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the temperature during fluorine doping is 1200℃ and the treatment time is 300min.
[0154] Example 10
[0155] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 9, except that the temperature during fluorine doping is 1300℃ and the treatment time is 300min.
[0156] Example 11
[0157] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the temperature during the second sintering is 1500℃, the holding time is 30min, and the temperature difference in the furnace is 3℃.
[0158] Example 12
[0159] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the temperature during the second sintering is 1600℃ and the temperature difference in the furnace is 1℃.
[0160] Example 13
[0161] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the holding time during the second sintering is 20 min.
[0162] Example 14
[0163] A low-loss optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that the holding time during the second sintering is 70 min.
[0164] Comparative Example 1
[0165] An optical fiber preform is prepared in a manner that is basically the same as that in Example 1, except that a first sintering is not performed.
[0166] The first intermediate, the second intermediate, and the optical fiber preform obtained during the preparation processes of the examples and comparative examples were subjected to the following tests. The test results are detailed in Table 1:
[0167] Fluorine radial concentration difference: The refractive index profile distribution is obtained by measuring the refractive index distribution in Chapter 7 of YD / T 4864-2024, and then the fluorine concentration is calculated from Δn; the fluorine concentration is obtained at four points in the radial direction: the mandrel, 1 / 4 radius, 1 / 2 radius, and cladding boundary, and the radial concentration difference is calculated.
[0168] Fluorine radial doping depth deviation: Based on the above fluorine concentration, the doping interface is fitted to obtain the fluorine doping depth, and the depth deviation (μm) is obtained by comparing it with the design depth.
[0169] Core alkali metal ion concentration: Measured according to GB / T-24575-2009 (TOF-SIMS detection of Na and K);
[0170] Radial diffusion depth of alkali metal ions: Analysis along the radial depth yielded Na⁺ and K⁺ concentration-distance curves; the concentrations were reduced to background values (≤1×10⁻⁶). 15 atoms / cm 3 The location corresponding to the diffusion interface is used to calculate the diffusion depth (μm).
[0171] Porosity: Refer to Chapter 9, Material Density and Defect Testing, in D / T-4864-2024;
[0172] Attenuation at 1550nm: Tested according to GB / T-9771-2020.
[0173] Table 1
[0174]
[0175] Depend on Figure 2 , Figure 3It can be seen that in the low-loss optical fiber preform prepared by the preparation method provided in this application, the refractive index of the core is basically the same as that of the surface layer. This indicates that the fluorine doping concentration in the core of the low-loss optical fiber preform is basically the same as that in the surface layer, and the fluorine has achieved good radial penetration, resulting in better doping uniformity.
[0176] As shown in Table 1, the low-loss optical fiber preform provided in this application has a porosity of less than or equal to 0.1%, the concentration difference of fluorine in the radial direction of the obtained low-loss optical fiber preform is less than 2.5 wt%, and the deviation between the doping depth of fluorine in the core and the doping depth on the cladding side is less than or equal to 0.3%, effectively eliminating refractive index distortion.
[0177] As shown by the attenuation data at 1550nm from the examples and comparative examples, the fabrication process provided in this application can stabilize the transmission loss of the low-loss optical fiber preform at a wavelength of 1550nm below 0.18dB / km, which is about 10% lower than that of optical fiber preforms obtained by conventional processes. Simultaneously, the alkali metal ion concentration in its core is less than or equal to 0.5ppb, thus solving the problem of alkali metal migration inwards.
[0178] In Example 8, the fluorine doping treatment temperature was 800℃, resulting in insufficient effective fluorine concentration, poor glass transition of the second intermediate, a hazy surface appearance, and uneven radial distribution of fluorine, which prevented the refractive index from remaining essentially uniform (e.g., ...). Figure 2 As shown, the refractive index plateau on the right exhibits curvature. This is because the fluorine doping treatment was carried out at a relatively low temperature, leaving a large amount of unreacted CF4 intermediates in the glass network, including CF3. + Free radicals accounted for 23.4%. These macromolecular free radicals hindered the densification of the glass network during subsequent sintering, leading to increased porosity in the resulting optical fiber preform. Simultaneously, due to the porous structure, the migration of alkali metal ions into the interior increased, resulting in a higher concentration of alkali metal ions in the core, causing distortion of the refractive index distribution and a decrease in transmission performance in the optical fiber preform.
[0179] Compared to Example 1, Comparative Example 1 did not undergo a first sintering, resulting in the second intermediate maintaining a porous structure (porosity greater than 1.0%). During the subsequent second sintering, the shallow layer (depth less than 20 mm) of the second intermediate was directly exposed to the environment, leading to an accelerated gas diffusion rate. Meanwhile, the inner layer, due to the cladding barrier, experienced a rapid decrease in fluorine permeation rate. Ultimately, the fluorine doping concentration difference between the inner and outer layers of the resulting optical fiber preform reached over 5.0%. This uneven fluorine doping concentration caused a significant stress gradient in the optical fiber preform during the second sintering process, such as... Figure 4The refractive index distribution exhibits an "M-shaped" distortion, with a refractive index depression of 0.002 at a radius of 1 / 4, resulting in a transmission loss of over 0.205 dB / km at a wavelength of 1550 nm.
[0180] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. A method for preparing a low-loss optical fiber preform, characterized in that, include: The silica porous body was subjected to dehydroxylation treatment to obtain the first intermediate; The first intermediate is subjected to fluorine doping treatment and first sintering in a fluorine-containing gas to obtain the second intermediate; The second intermediate is subjected to a second sintering in a mixed atmosphere of inert gas and fluorine-containing gas to obtain the low-loss optical fiber preform. The temperature of the first sintering is lower than the temperature of the second sintering.
2. The preparation method according to claim 1, characterized in that, The porous silica body comprises a core rod and a deposited layer, the density of which is 0.28 g / cm³. 3 -0.40g / cm 3 ; And / or, the second intermediate contains fluorine, and the radial concentration difference of the fluorine in the second intermediate is less than or equal to 8%; And / or, the porosity of the second intermediate is less than or equal to 5%.
3. The preparation method according to claim 1 or 2, characterized in that, The temperature for the dehydroxylation treatment is 1100℃-1300℃.
4. The preparation method according to any one of claims 1-3, characterized in that, The heating rate for the dehydroxylation treatment is 10℃ / min-15℃ / min.
5. The preparation method according to any one of claims 1-4, characterized in that, The temperature of the fluorine doping treatment is less than or equal to the temperature of the dehydroxylation treatment.
6. The preparation method according to any one of claims 1-5, characterized in that, The temperature of the first sintering is greater than or equal to the temperature of the fluorine doping treatment.
7. The preparation method according to any one of claims 1-6, characterized in that, The process further includes a first cooling and / or a second cooling after the second sintering: The cooling rate of the first cooling is 50℃ / min-100℃ / min; The starting temperature for the second cooling is 800℃-1000℃.
8. A low-loss optical fiber preform, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
9. The low-loss optical fiber preform according to claim 8, characterized in that, The porosity of the low-loss optical fiber preform is less than or equal to 0.1%; And / or, the low-loss optical fiber preform is doped with fluorine, and the radial doping depth deviation of the fluorine in the low-loss optical fiber preform is less than or equal to 0.3%.
10. The low-loss optical fiber preform according to claim 8 or 9, characterized in that, The low-loss optical fiber preform includes alkali metal ions; The radial diffusion depth of the alkali metal ions in the low-loss optical fiber preform is less than or equal to 300 μm. And / or, the low-loss optical fiber preform includes a core, wherein the concentration of the alkali metal ions in the core is less than or equal to 0.6 ppb.
11. A low-loss optical fiber, characterized in that, The low-loss optical fiber preform according to any one of claims 8-10 is prepared by stretching, wherein the radial distribution concentration difference of fluorine in the low-loss optical fiber is less than or equal to 2.5%.
